Exploring the Use of Technology-Enhanced Language Learning Tools in ESL Classrooms in the KSA - Nouf Abdulrahman Almohideb (Yayasan Visi Intan Permata, 2025)
The aim of the study to explore the role of using TELL tools in facilitating ESL classes and their usefulness and implementation in teaching-learning. This study has used cross-sentional research design using quantitative research approach using purposive sampling method. The population of the study was ESL students of universities in the KSA. Survey questionnaire was used to collected primary data from 202 ESL students. In order to analyse data, statistical analysis has been used such as frequency distribution, statistical descriptive, correlation matrix, Chi-square, and T-test. Findings revealed that TELL tools are valued for their support of engagement enhancement, improvement in language skills, and flexible learning opportunities. Apps related to grammar and vocabulary became the most utilized. Mobile applications and online websites are considered predominant tools. Limited access to the device, technical problems, and difficulty navigating are challenges toward successful implementation. Nevertheless, a huge benefit that the participants encountered included increased motivation, enjoyment, and vocabulary improvement. The study concludes that TELL tools are pivotal in enriching ESL learning experiences but require improved accessibility, usability, and teacher training for broader adoption. This study will be helpful to educators, policymakers, and technological product designers only by understanding the effects of its applications on the learner.